Pemenuhan Kualitas Ruang Terbuka Hijau Publik Di Kota Bogor - Hidayat, Janthy Trilusianthy (Publikasi Indonesia, 2025)
According to Bogor City RTRW for 2011 – 2031, the city’s green open space is allocated 20% or around 2,229.63 Ha of the total area of Bogor City. Existing area of green open space in Bogor City is 468,18 Ha. The need for urban space is increasing every year, while the limited availability of urban space causes green open spaces in urban areas to decline because they become functional buildings which cause a decline in function and environmental balance in urban areas. In an effort to fulfill the quality of public green open space in the city of Bogor, research was conducted with the aims of (1) identifying the exisiting condition of public green open space in the city of Bogor (2) Identifying green open space based on oxygen needs in the city of Bogor (3) Analysis of the fufillment of the quality of public green open space in the city of Bogor based on distribution exixting green open spaces, green open space besed on the quality vegetation density, and green open space requirements based on oxygen.As for the results of this reseacrch, based on the existing conditions of green open space, not all sub-districts have 20% green open space, the looking at green open space based on oxygen needs, the largest green open space required is in West Bogor District, then the sub-district with the smallest green open space requirement is in Central Bogor District. Fulfillment of the quality of green open space is divided into 3 categories good, sufficient, and poor green open space.